ANALISIS PERILAKU KOMUNIKASI MAHASISWA TERHADAP BERMAIN GAME ONLINE MOBILE LEGENDS DI UNIVERSITAS ESA UNGGUL KAMPUS TANGERANG - Monica Ellena; Thessalonika Shereen Olivia (Cahaya Ilmu Bangsa, 2025)
The advancement of digital technology and the widespread use of the internet have transformed the communication patterns of younger generations, including through online games such as Mobile Legends: Bang Bang. This game serves not only as entertainment but also as a significant platform for social interaction. This study aims to analyze the communication behavior of students at Universitas Esa Unggul Tangerang while playing Mobile Legends, focusing on verbal, nonverbal, and virtual communication forms and their impact on social relationships and communication skills. This research is grounded in communication theory (Soewarno, 1980), which distinguishes between verbal, nonverbal, and virtual communication, as well as social interaction and motivation theories. The type of research employed is descriptive qualitative, with data collected through participant observation, in-depth interviews, and questionnaires. The respondents were active students who regularly play Mobile Legends. The findings reveal that students are motivated to play Mobile Legends for entertainment, social interaction, and peer recognition. Verbal communication is more frequently used when playing with close friends, while nonverbal communication is employed for coordination with new players. The game also enhances teamwork skills, conflict management, and interpersonal communication abilities. However, high playing intensity poses a risk of lowering academic performance and disrupting real-world social relationships. This study provides insights into how online games can influence students' communication patterns and offers recommendations to optimize the positive impacts of this activity.